2015
DOI: 10.1590/1807-2577.1027
|View full text |Cite
|
Sign up to set email alerts
|

Identificação das espécies de Candida em portadores de estomatite protética e avaliação da susceptibilidade ao miconazol e à terapia fotodinâmica

Abstract: INTRODUÇÃO: Próteses mucossuportadas são consideradas facilitadoras, em potencial, da estomatite protética (EP), condição caracterizada pelo aspecto eritematoso, difuso ou pontilhado da mucosa palatina sob a base das próteses. A etiologia da doença é multifatorial, embora a infecção por Candida seja uma causa bastante comum. OBJETIVO: Relacionar a EP com a presença de Candida, identificar as espécies de Candida mais prevalentes, a partir do meio CHROMagar Candida(r), e caracterizar o perfil de sensibilidade da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 22 publications
2
12
0
6
Order By: Relevance
“…Regarding the prevalence of species, our findings corroborate studies that showed Candida albicans as the primary etiological agent of denture stomatitis [2, 21, 27, 36, 4749]. …”
Section: Discussionsupporting
confidence: 89%
“…Regarding the prevalence of species, our findings corroborate studies that showed Candida albicans as the primary etiological agent of denture stomatitis [2, 21, 27, 36, 4749]. …”
Section: Discussionsupporting
confidence: 89%
“…Abundant fungal structures are observed in specimens obtained from the surface of complete removable dental prostheses. This fact allows us to infer that inadequate use of prostheses, together with inadequate hygienization favor the growth of genus Candida yeasts, particularly C. albicans 9 , 10 , 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Candida albicans is the most well-known fungal species associated with the clinical manifestation of this pathology. In addition to C. albicans , other less common Candida spp., such as C. tropicalis , C. glabrata , C. parapsilosis , and C. krusei , are pathogens present in the oral microbiota that can become pathogenic [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%